International market selection model using newly developed geometric international market selection space - Hussein, Mazlan (2019)
International Market Selection (IMS) is literally a process in identifying and selecting feasible international market opportunities for exporting. It is a methodological process whereby suitable variables are vetted through a model in order to produce output in the form of processed information that would help export marketers in decision making. Literatures affirm that there are many IMS models available. Focusing on detailed literature review of prominent models reveals that there are inherent shortcomings in addressing market selection. The utilisation of too many input variables in the filtering and weighting scheme makes the process of IMS complex, cumbersome and bias. It is the main objective of this thesis to propose a new IMS model in attempt to address these weaknesses. The pinnacle of this thesis consisting of closely related chapters is the design and construction of a new Trade Intensity (TI) index for possible use in international market selection. The design and construction of the TI index is geometrically illustrated using a newly constructed Geometric Trade Intensity Space Box (GTISB). The new IMS model, introduced as Geometric International Market Selection Space (GIMSS), rooted from the TI index and GTISB is proposed as a complimentary tool for use by international marketers. In principal it utilises two trade base elements (import and export) as input variables. The GIMSS model is designed to consist of five stages and is capable of processing secondary data either Standard International Trade Classification (SITC) or Harmonised System (HS). The result can be transpired and visualised into a geometrical space square box for any number of products or period of study. A comparative performance analysis of this new approach with a previous study (see Tong (2012)) is also conducted. Results indicated firstly the absence of import elements and the absence of some key filtering elements in the previous study. In contrast, this thesis offers new elements in IMS modelling, in particular new tools in identifying International Export Opportunities (IEO). The constructed GIMSS model utilises both trade elements (exports and imports) with no filtering and weighting processes, employs changes within changes measurement, embeds quality perspective measurement as alternative game changer in identifying IEO, and able to do future projection of IEO. In addition, even though this GIMSS model does not have weighting scheme, it can still perform trade-off process between volume and quality elements. This would allow marketers with flexibility to trade-off strategy application impartially. Furthermore this new GIMSS approach enables the possibility of being utilised in cross sectional studies using simple calculations while maintaining the triad essentials of symmetry, scaling, and proportionality in the analysis. As such, these features of the new model enables the visualisation of changing IEO patterns throughout the analytical space with consistent, copious and yet easy to interpret results. From the findings of this thesis, there are two potential policy implications that policy makers may apply in legislating policy and decision making process. Firstly, the GIMSS is capable of identifying and categorising the host country market potential into low, intermediate or high market potential at product level. With that policy maker would be able to employ this information conjointly with competitive index of exporting country and make assessment in the perspective of cross checking between host country market potential levels with exporting country competitive advantage status. Thus policy makers would have a better vision in developing more effective and well organised marketing strategy and resource allocation. Secondly, GIMSS is capable of identifying niche market potential of high risk country. Thus policy makers may set a new direction of not to filter out the high risk countries from their potential and explore them for either market expansion or new market breakthrough. In summary, this paper addressed the existing shortcomings of prominent IMS models in the literature in particular the Green and Allaway (1985) shift-share model, the Papadopoulos, Chen and Thomas (2002) trade-off model, and the decision support models of Cuyvers, De Pelsmacker, Rayp and Roozan (1995) and Cuyvers (2004) and proposed the new GIMSS model consisting of the TI index and the GTISB extending earlier work done in the literature.